Analisis Sistem Informasi Akuntansi Penerimaan Kas Terhadap Efektivitas Pengendalian Intern Pendapatan Jasa Pada Perusahaan Transportasi (Studi Kasus Pada PT. Lancar Sejahtera Abadi) - Tita Puspita Maharani; Noor Shodiq Askandar; Junaidi Junaidi (e_Jurnal Ilmiah Riset Akuntansi, 2023)
PT. Lancar Sejahtera Abadi (LSA) established in 2008, is a Transportation Management Services company. Namely transportation services and goods delivery that are integrated using a combination of land transportation modes. This company stands from a combination of reliable professionals, supported by all partners and human resources who are trained and tested to place at PT. Lancar Sejahtera Abadi (LSA) as a complete, reliable and trusted transportation service provider company.This study aims to determine the accounting information system for cash receipts to the effectiveness of internal control of service income in transportation companies PT. Lancar Sejahtera Abadi (LSA). Types of research used in this study is descriptive qualitative. The data and information processed are data obtained from the results of structured interviews and documentation that will be analyzed qualitatively and described in a descriptive form.Based on the results of the study, the cash receipt accounting information system at PT. Lancar Sejahtera Abadi is said to be relatively good, this can be seen where PT. Lancar Sejahtera Abadi has implemented systemized recording in each division and in accordance with the procedures of the cash receipt accounting information system.Keywords : Cash receipt accounting information system; accounting information system; revenue control; service income; cash receipts